2015
DOI: 10.1177/0192513x15579502
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Cost of Emotional Support? The Association Between Intensive Mothering and Psychological Well-Being in Midlife

Abstract: Studies of intensive mothering suggest that fulfilling societal expectations of the “good mother” diminishes maternal psychological well-being; however, studies tend to focus on young mothers. We examine the association between intensive mothering and psychological well-being using a sample of mothers in midlife (n = 1,388) drawn from the 2004-2006 National Survey of Midlife Development in the United States. Intensive mothering is measured as provision of high levels of emotional support to children, high degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 27 publications
1
58
0
1
Order By: Relevance
“…Teacher-mothers take on a tremendous responsibility and a large amount of unpaid labor, which can have substantial effects on their mental health (Henderson, Harmon, & Newman, 2015;Lois, 2013). The added pressure of their added work could exacerbate the anxiety, depression, and life dissatisfaction already proven to be related to mothering (Gunderson & Barrett, 2015;Hays, 1996;Lois, 2013). Of course, there has been research conducted that suggests that depression is not experienced at higher rates for nonparents than their child-free peers (Nomaguchi & Milkie, 2003;Simon & Caputo, 2018) indicating that the nature of parenting and mental health is complex and warrants more exploration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teacher-mothers take on a tremendous responsibility and a large amount of unpaid labor, which can have substantial effects on their mental health (Henderson, Harmon, & Newman, 2015;Lois, 2013). The added pressure of their added work could exacerbate the anxiety, depression, and life dissatisfaction already proven to be related to mothering (Gunderson & Barrett, 2015;Hays, 1996;Lois, 2013). Of course, there has been research conducted that suggests that depression is not experienced at higher rates for nonparents than their child-free peers (Nomaguchi & Milkie, 2003;Simon & Caputo, 2018) indicating that the nature of parenting and mental health is complex and warrants more exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Gunderson and Barrett () found that depressive symptoms were more likely to be reported by mothers who spent more time supporting their children emotionally. This tension can cause conflicting feelings of joy and love for their children but also depression, frustration, and a loss of self and freedom (Arendell, ; Donath, ).…”
Section: Stigma Management Emotional Management and Fear Of Failurementioning
confidence: 99%
“…Another study, using the 1981 to 2008 European Values Survey, showed that the positive effects of parental status on life satisfaction decreased during this period (Ugur, ). Several studies that used convenience samples examined the effects of intensive parenting beliefs on mothers' well‐being and found that mothers who believed in or enacted intensive parenting ideologies were more likely to report feeling anxious, guilty, stressed, and depressed (e.g., Gunderson & Barrett, ; Liss, Schiffrin, Mackintosh, Miles‐McLean, & Erchull, ; Rizzo, Schiffrin, & Liss, ). Yet, concepts and measures of intensive parenting ideology varied widely across these studies.…”
Section: Changing Norms Of Parentingmentioning
confidence: 99%
“…Parenting role overload, defined as the perception that the amount of child‐care demands exceeds the individual's capacity, is often measured as respondents' perceptions of feeling overwhelmed (e.g., “Being a parent is harder than I thought it would be”; Luthar & Ciciolla, ). Parent–child relationship conflict is a strong stressor that affects parents' mental health negatively (Gunderson & Barrett, ; Luthar & Ciciolla, ; Reczek & Zhang, ). On the flip side, not discussed in the SPM and underscoring a demands–rewards perspective, close parent–child relationships act as “rewards” that enhance parents' well‐being (Nomaguchi, ).…”
Section: The Demands and Rewards Of Parentingmentioning
confidence: 99%
“…Furthermore, most of the research that has explored the negative emotional costs of intensive mothering has focused on the experiences of mothers with young children, but pressure to mother intensively has been documented throughout mothers’ lives (Gueta, ; Peled, Gueta & Sander‐Almoznino, ; Gunderson & Barrett, ), particularly when children have problems (Greenfield & Marks, ). For example, in a study with mothers between the ages of 35 and 60 years, Dillaway () concluded that ‘mother work perhaps never wanes: once women are mothers, they are always mothers, and they are always impacted by the mothering ideology’ (p. 51).…”
Section: Introductionmentioning
confidence: 99%